ROLE OF PALLIATIVE RADIOTHERAPY IN IMPROVING PERFORMANCE STATUS AND QUALITY OF LIFE IN PATIENTS WITH METASTATIC SPINAL CORD COMPRESSION - Qamar, Fawad Ul; Sajjad, Kashif; Haider, Irfan; Khan , Fattah Ullah; Inam, Yasir; Anjum, Maheen (Journal of Ayub Medical College Abbottabad, 2022)
Background: Palliative radiotherapy in patients with metastatic spinal cord compression is a well-known treatment modality but little is known whether it improves quality of life and performance status. Our study focusses on analyzing the impact of palliative radiotherapy on these two parameters in patients with metastatic spinal cord compression. Methods: We performed a prospective observational study from August 2020 to April 2021 to assess consecutive patients presenting to emergency department with suspected MSCC. We enrolled 24 patients in the study, and they were evaluated for their performance status and quality of life using ECOG and FACIT-PAL 14 scores respectively. Palliative radiotherapy was administered, and the patients were followed up four to six weeks later. Their ECOG and FACIT-PAL 14 scores before and after receiving palliative radiotherapy were analyzed. Results: The mean age of the patients was 48 (IQR 35-62), with 14 (58%) being male. 1 patient died soon after admission. Median dose fractionation was 2000 cGy. Median (IQR) of ECOG performance status score on admission and follow up was 2.5 (1.0-3.7) and 1.5 (1.0-3.7), p=0.719, respectively. Median (IQR) FACIT-PAL 14 score on admission and follow up were 35.5 (34.0-37.6) and 36.5 (30.2-44.7), p=0.277, respectively. Our results indicate that there was no statistically significant difference in the median ECOG performance status and FACIT PAL 14 scores before and after the administration of palliative radiotherapy. Conclusion: Our study indicates that palliative radiotherapy in patients with metastatic spinal cord compression had little benefit in objectively improving quality of life and performance status using the well-known and widely used scores. This lack of response could be due to delayed presentation of the patients. Earlier involvement of palliative care team could have improved both these parameters. Further research with larger population of patients over a longer period is needed to further assess these outcomes.